Pengaruh Kepuasan, Komitmen Kalkulatif, Komitmen Afektif, dan Kepercayaan terhadap Kesetiaan Konsumen Studi Kasus pada Pelatihan Kursus Bahasa ELTI di Yogyakarta - , ASTRID MAYASARI, Bayu Sutikno, M.S.M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Increasingly organization are recognizing the value of establishing close relationships with their customers. Despite this, research has not deeply explored how the intangible aspects of relational exchange such as customer satisfaction, as well as calculative commitment, affective cimmitment and trust, combine to determine loyalty.The purpose of the current study is to address these issues and to demonstrate how a relational marketing orientation can assist education service management. This is in part a result of reluctance within the sector approach and a sample of 474 students to examine, firts the determinants of loyalty and second, the role of relationship strength as a moderator of those determinants. The result indicate that student loyalty was most strongly determined by psychological attachment, and a sense of belonging to the brand. Student satisfaction, while a contributing determinant, alone was insufficient in generating loyalty. The result also indicated that students rejected the notionof loyalty determined by inertia and high switching costs. In addition, trust was not found to be a strong determinant of recommendation or return.